VALOR NUTRITIVO DE VARIEDADES DE CANA-DE-AÇÚCAR EM FUNÇÃO DA ADUBAÇÃO NITROGENADA - COSTA, Mayanna Karlla Lima (2014)
The objective was to evaluate the nutritional value of varieties of sugar cane as a function of nitrogen fertilization. The varieties used were RB 863129, RB 867515 and RB 92579 and the nitrogen doses were 0, 60, 80, 120 and 140 kg ha-1. The experiment was divided in two stages: in the stage we evaluated the productivity and nutritional quality of three varieties of sugar cane (I Year - plant cane), and in the second stage (Years II and III) we evaluated the influence of nitrogen fertilization on the nutritional quality of the first and second ratoon of the same sugar cane varieties. For the analysis of productivity and other parameters, one collection of plant material was performed at the end of each experimental. The laboratory analysis consisted in the dry matter (DM), crude protein (CP), neutral detergent fiber (NDF), acid detergent fiber (ADF) and (DMIVD) digestibility. In plant cane were also determinations of Brix and ratio NDF/Brix. For the plant cane, in terms of productivity in t ha-1, percentage of DM and CP, we observed a better values (P<0.05) for the RB 863129, and there was no significant difference between varieties (P <0.05) for the NDF, ADF and DMIVD. The three varieties evaluated showed reasonable chemical composition for ruminant nutrition and in vitro digestibility greater than 60%. The first and second ratoon all parameters differed (p<0.05) between varieties and fertilization, with the exception of DM content and in vitro digestibility occurring in most cases significant interaction between varieties, treatment and years of cutting. The variety RB 92579 presented at the two brass knuckles better productivity (a 131 t ha-1 of stalks) coupled with the best nutritional parameters (26% of ADF, 41% NDF, 2,44% CP and 69 DMIVD). The productivity of cane sugar, as well as its nutritional quality may suffer any increase or decrease according to the year and cutting management established in relation to nitrogen fertilization, moreover, the observed responses were influenced by varieties in most parameters assessed.